Solving the core theoretical issues in consumer behavior in tourism - Woodside, Arch (2017)
© 2017 by Emerald Publishing Limited. Consumer behavior in tourism (CBT) is an interdisciplinary field of study encompassing the basic behavioral and economic sciences (e.g., psychology, sociology, and economics) and applied fields of study (e.g., management, marketing, tourism, and hospitality) focusing on all aspects of discretionary travel. This chapter describes major issues and findings in the literature relating to CBT. The chapter directs the reader's attention to some of the highly-cited studies in this literature - these studies provide a foundation of knowledge on the central topics, issues, methods, findings, and theoretical/ practical contributions in research on CBT. Research studies in CBT focus on one-to-all five core theoretical issues in basic and applied fields of study: describe who is doing what, when, where, how, and the consequences of the activities; explain the meanings of activities and motivations of the actors; predict (model) what actions and outcomes will occur and the impacts of influence attempts before, during, and after engaging in tourist actions; control (influence) the beliefs, attitudes, behaviors, and assessments of tourists, local community members, and additional stakeholders; evaluate tourism service/product delivery, tourism management performance, and customer satisfaction. Survey research using verbal (written) responses to questions is pervasive and the most frequent method for data collection in CBT. Additional research genres in CBT include direct observations of tourism behavior with or without some oral questioning (unobtrusive studies, the long interview method (McCracken, 1988), use of "consumer culture theory"), participant observation including semester abroad and unpaid internships away from home, formal field experiments, and the study of secondary sources (e.g., photographs and writings in blogs and social media (e.g., TripAdvisor) reviews).